Ultra‐Sensitive Bio‐Polymer Iontronic Sensors for Object Recognition from Tactile Feedback - Cicek, Melih Ogeday; Durukan, Mete Batuhan; Yıldız, Bayram; Keskin, Deniz; Doganay, Doga; Çınar Aygün, Simge; Cakir, Murat Perit; Unalan, Husnu Emrah (Advanced materials technologies, 2023)
Supramolecular polymer gels show promise for use in batteries, supercapacitors, and multifunctional sensors. However, their poor stiffness and ionic conductivity hinder their large‐scale utilization. Herein, a cellulose‐based supramolecular bio‐polymer gel (SBPG) with high ionic conductivity and exceptional stiffness is reported. These properties are translated into proof‐of‐concept iontronic pressure sensors with an ultra‐high sensitivity of 1 475 000 kPa−1. The technological potential is demonstrated via fabrication of a prototype smart glove using only eight pressure sensors based on this novel gel. Smart glove sensors with 90% classification accuracy for object recognition are demonstrated using a tactile feedback algorithm. Cellulose‐based supramolecular bio‐polymer gels with high ionic conductivity (9.85 x 10-4 S cm-1)  are fabricated. Developed supramolecular bio‐polymer gels are used for an ultra‐high sensitivity iontronic pressure sensor with a sensitivity of 147 500 kPa−1. Pressure sensing mechanism of the sensors is extensively investigated with 3D Bode analysis. The sensors are used to develop a smart glove for object recognition.